50.8k views
5 votes
Pls help!!! if f(x) = 3x-2 and g(x) = 6-4x, fibd f(x) + g(x)

Pls help!!! if f(x) = 3x-2 and g(x) = 6-4x, fibd f(x) + g(x)-example-1
User Moory Pc
by
6.3k points

2 Answers

2 votes
f(x) = 3x-2
g(x) = 6-4x

f(x) + g(x) = 3x-2+6-4x = - x +4 =4 - x

Answer B.4-x
User Vitooh
by
6.1k points
4 votes
So first off the equation we are solving is f(x) + g(x). So i want to plug in those equations first off. The new equation I get should be 3x-2 + 6 -4x. I then simplify this to -x+4 or 4-x.
User AlexGeorg
by
6.3k points